Analysis of Tissue-Specific Defense Responses to Sclerotinia sclerotiorum in Brassica napus - Jie Liu; Rong Zuo; Yizhou He; Cong Zhou; Lingli Yang; Rafaqat Ali Gill; Zetao Bai; Xiong Zhang; Yueying Liu; Xiaohui Cheng; Junyan Huang (Plants, 2022)
Sclerotinia stem rot (SSR) caused by Sclerotinia sclerotiorum (S. sclerotiorum) is the main disease threat of oilseed rape (Brassica napus), resulting in huge economic losses every year. SSR resistance manifests as quantitative disease resistance (QDR), and no gene with complete SSR resistance has been cloned or reported so far. Transcriptome analysis has revealed a large number of defense-related genes and response processes. However, the similarities and differences in the defense responses of different tissues are rarely reported. In this study, we analyzed the similarities and differences of different tissues in response to S. sclerotiorum at 24 h post inoculation (hpi) by using the published transcriptome data for respective leaf and stem inoculation. At 24 hpi, large differences in gene expression exist in leaf and stem, and there are more differentially expressed genes and larger expression differences in leaf. The leaf is more sensitive to S. sclerotiorum and shows a stronger response than stem. Different defense responses appear in the leaf and stem, and the biosynthesis of lignin, callose, lectin, chitinase, PGIP, and PR protein is activated in leaf. In the stem, lipid metabolism-mediated defense responses are obviously enhanced. For the common defense responses in both leaf and stem, the chain reactions resulting from signal transduction and biological process take the primary responsibility. This research will be beneficial to exploit the potential of different tissues in plant defense and find higher resistance levels of genotypic variability in different environments. Our results are significant in the identification of resistance genes and analysis of defense mechanisms.